2014
DOI: 10.1016/j.rboe.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as a prognostic factor for fracturing of the proximal extremity of the femur: a case–control study

Abstract: ObjectivesTo compare the body mass index (BMI) of patients with fractures in the proximal extremity of the femur with the BMI of patients without any previous history of fractures.MethodsWe investigated patients of both sexes, aged 65 years or over, who were admitted to Hospital Independência, Hospital Beneficência Portuguesa or ULBRA University Hospital, between December 2007 and December 2010, with histories of low-energy trauma such as falling from a standing position. These individuals were compared with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Assessed on panoramic radiographs, MCI is widely advocated as appropriate for detecting osteoporotic alterations. 18,20,[34][35][36] BMI 24,37 and age are strongly correlated with BMD status, 23,38,39 although other factors may still influence BMD, such as sunlight exposure, sedentary lifestyle, body type or excessive coffee intake. 40 Actively studied in the literature, these main points were highlighted to assess Brazilian postmenopausal women with different ethnicities.…”
Section: Number Of Participantsmentioning
confidence: 99%
“…Assessed on panoramic radiographs, MCI is widely advocated as appropriate for detecting osteoporotic alterations. 18,20,[34][35][36] BMI 24,37 and age are strongly correlated with BMD status, 23,38,39 although other factors may still influence BMD, such as sunlight exposure, sedentary lifestyle, body type or excessive coffee intake. 40 Actively studied in the literature, these main points were highlighted to assess Brazilian postmenopausal women with different ethnicities.…”
Section: Number Of Participantsmentioning
confidence: 99%
“…While, Cunha and Veado (17) analyzed 190 patients (142 women and 48 men; mean age of 79 years) in the state of Minas Gerais, Brazil who were hospitalized with fractures in the proximal extremity of the femur in the orthopedic ward, among whom the incidence of trochanteric fractures was 50%, femoral neck fractures 44% and subtrochanteric fractures 6%. In contrary, Pagani et al (4) revealed that the main types of fracture presented in their study were trochanteric fractures, with 47 cases (62.2%), followed by femoral neck fractures 27 cases (36%) then subtrochanteric fractures, with one case only (1.8%).…”
Section: Discussionmentioning
confidence: 70%
“…While Fini et al (14) revealed that overweight and obesity protect bone, thus reducing the fracture risk and the development of osteoporosis in older adults. On the other hand, a case-control study performed by Pagani et al (4) revealed that, among the patients with proximal fractures of the femur, 5.6% presented low weight, 43.8% normal weight, 33.7% overweight, and 9.8% obesity. Also, a study conducted by Alfaro-Acha et al (1) confirmed that there was an inverse relationship between body weight and the risk of fracturing of the proximal extremity of the femur and reported that a 10% weight loss significantly increased the risk of hip fractures among individuals aged 65 years and over.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The secretion of estrogen rapidly declines after menopause and leaves postmenopausal women (PMW) at a higher risk of various physical and mental illnesses compared with men (7) . Thus, osteoporosis ends up being a common disease in postmenopausal women due to age and hypoestrogenism, with an increased prevalence and incidence of fractures and hence a negative effect on the quality of life of such women (8) .…”
Section: Introductionmentioning
confidence: 99%